Knowledge, Attitudes and Practices of Licensed Dog Breeders in Kansas Regarding Canine Brucellosis - Crow, Allison (My University, 2013)
Background: Canine brucellosis is an infectious reproductive disease of dogs and is zoonotic. Cases of disease in dogs and humans are reportable to the Kansas Department of Agriculture – Division of Animal Health (KDA-DAH) and the Kansas Department of Health and Environment (KDHE), respectively. People with occupational exposures, such as dog breeders, are more likely to be exposed to this bacterium. It can be difficult to diagnose in humans; the true incidence is not well understood. The objectives of this study were to understand the knowledge, attitudes and practices (KAP) of breeders regarding canine brucellosis and to determine the human incidence of infection in Kansas. Methods: A KAP survey was mailed to all 294 licensed breeders in Kansas. We evaluated all case reports of human brucellosis reported to KDHE from 1997-2012. Results: The response rate was 25.5% (75/294). Eighty-eight percent of breeders (66/75) had knowledge of canine brucellosis. Only 66.7% (44/66) of those knew it was zoonotic; they were not more likely to wear gloves during whelping (p = 0.4156). Seven breeders (9.33%) reported cases of brucellosis in dogs; no respondents reported symptoms of canine brucellosis. Eleven confirmed, sixteen probable and twenty-eight suspect human cases of brucellosis have been reported in Kansas; 81% (22/27) did not report a specific species of Brucella. Conclusions: Breeders are knowledgeable about canine brucellosis; however, they were not more likely to take appropriate personal protective measures. Public and animal health officials should be aware that dogs can serve as a source of brucellosis infection to people.
Keywords: Public Health; Canine Brucellosis; Dog Breeders; Public Health (0573)